Integrated pest management in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Integrated pest management in the Tropics: current status and future prospects edited by A N Mengech K N Saxena and H N B Gopalan 1995 171pp ISBN 0471 96976 4